Timing of fission in the starfish Allostichaster capensis (Echinodermata:Asteroidea) in laboratory - Rubilar Panasiuk, Cynthia Tamara (2006)
Timing of fission in the fissiparous starfish Allostichaster capensis under laboratory conditions is described. A. capensis generally splits across the disc along the fission plane during the spring, and then each half regenerates the missing arms during the rest of the year. The fission process can last eight hours. The healing process starts immediately after fission. A. capensis has impressive regeneration ability, including a comet, without signs of disc, regenerated two new arms.